Hydrolysis to Recover Protein for Efficient Utilization of Shrimp Waste - Xiao'e Chen; Xubo Fang; Yamei Jiang; Jing Chen; Hui Yu; Zhi Liao (2011 International Conference on Computer Distributed Control and Intelligent Environmental Monitoring, 2011)
Chitin and chitosan production has been reported to be an economical technique to utilize the shrimp waste. Amajor fraction of the shrimp waste is tissue protein and seldom research investigated to recover the protein fraction through hydrolysis by using protease. This paper described the hydrolysis treatment of shrimp processing waste with Pepsin(1000 U/g), under 35°C, pH 4 for 3h. By this method the degree of hydrolysis reached to 48.6%. The protein-rich material can be used as an animal feed supplement. Furthermore, it has proven environmentally attractive for the alkali volume and liquid waste was sharply reduced through this method.